2012
DOI: 10.1158/0008-5472.can-12-1653
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Overfeeding Affecting Both Tumor and Systemic Metabolism Activates the Progesterone Receptor to Contribute to Postmenopausal Breast Cancer

Abstract: Obese postmenopausal women have increased risk of breast cancers with poorer clinical outcomes than their lean counterparts. However, the mechanisms underlying these associations are poorly understood. Rodent model studies have recently identified a period of vulnerability for mammary cancer promotion, which emerges during weight gain after the loss of ovarian function (surgical ovariectomy; OVX). Thus, a period of transient weight-gain may provide a lifecycle-specific opportunity to prevent or treat postmenop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 49 publications
10
86
0
Order By: Relevance
“…Recently, FGFR1 was reported to interact with ER in the cytoplasm and nucleus of endocrine-resistant breast cancer cells, suggesting that ER remains functional through growth factor pathway activation, despite estrogen deprivation (14). Taken together, these observations support a dual-requirement hypothesis that we have previously presented (38,47), in which metabolic impairment associated with obesity converges with a positive energy balance following estrogen deprivation to form a tumor-promoting environment (Figure 7). To tackle this problem clinically, it may only be necessary to improve metabolic function, either pharmacologically or through exercise, or to prevent EWD-induced weight gain.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, FGFR1 was reported to interact with ER in the cytoplasm and nucleus of endocrine-resistant breast cancer cells, suggesting that ER remains functional through growth factor pathway activation, despite estrogen deprivation (14). Taken together, these observations support a dual-requirement hypothesis that we have previously presented (38,47), in which metabolic impairment associated with obesity converges with a positive energy balance following estrogen deprivation to form a tumor-promoting environment (Figure 7). To tackle this problem clinically, it may only be necessary to improve metabolic function, either pharmacologically or through exercise, or to prevent EWD-induced weight gain.…”
Section: Discussionsupporting
confidence: 76%
“…A rodent model study demonstrated that obese animals deposited excess nutrients into tumors, and increased expression of PR was positively correlated with glycolytic and lipogenic enzymes from tumors (15). In a retrospective study in Asia, it was observed that obese women experience more advanced disease with higher axillary lymph node ratio and higher stage at diagnosis (16).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the association between increased incidences of breast cancer and obesity in women remains poorly understood, but a growing body of evidence suggests that insulin resistance, chronic inflammation, estrogen and adipokine interaction may be involved (14). An expression array analysis of breast tumor tissues from postmenopausal women demonstrated that progesterone receptor (PR) expression correlated with metabolic upregulation of glucolysis and lipogenesis (15). Furthermore, it has been identified that obesity is correlated with estrogen receptor (ER) and PR expression, thus supporting their underlying associations (16).…”
Section: Introductionmentioning
confidence: 97%
“…Clinical trials are ongoing to study the anti-cancer effect of dietary fat reduction and physical exercise (Table 1). Chronic inflammation is related to the development of various cancer types (Giles et al, 2012). In two case-control studies with in total almost 2000 post-menopausal women, systemic levels of the aspecific inflammatory marker C-reactive protein or soluble tumor necrosis factor receptor 2 were associated with overweight and increased breast cancer risk (Gross et al, 2013;Ollberding et al, 2013).…”
Section: Obesity and Inflammation -Clinical Datamentioning
confidence: 99%
“…Metformin indeed diminishes the growth of breast cancer cells in vitro (Zakikhani et al, 2006). In obese rats in which mammary tumor growth was induced by 1-methyl-1-nitrosourea injection, metformin treatment reduced tumor burden (Giles et al, 2012). Insulin and hyperinsulinemia can also promote tumorigenesis indirectly by influencing the levels of other modulators, such as IGFs, sex hormones, inflammatory processes and adipokines (Jalving et al, 2010).…”
Section: Insulin -Mechanism Of Action and Preclinical Datamentioning
confidence: 99%